The Relationship Between Line Manager Behavior, Perceived HRM Practices, and Individual Performance: Examining the Mediating Role of Engagement. Issue 6 (November 2013) - Alfes, Kerstin; Truss, Catherine; Soane, Emma C.; Rees, Chris; Gatenby, Mark; Brewster, Chris; Gollan, Paul J.; Wright, Patrick M.
Abstract This article examines the role played by line managers in the link between HRM practices and individual performance outcomes. Drawing on social exchange theory, the authors test a mediated model linking perceived line manager behavior and perceived human resource management practices with employee engagement and individual performance. The study focuses on two self‐report measures of individual performance; task performance and innovative work behavior. Two studies with a total of 1, 796 participants were conducted in service‐sector organizations in the United Kingdom and analyzed using structural equation modeling. The data reveal that perceived line manager behavior and perceived HRM practices are linked with employee engagement. In turn, employee engagement is strongly linked to individual performance and fully mediates the link between both perceived HRM practices and perceived line manager behavior and self‐report task performance (study 1), as well as self‐report innovative work behavior (study 2). The findings show the significance of the line manager in the HRM‐performance link, and the mediating role played by employee engagement. © 2013 Wiley Periodicals, Inc.